2004
DOI: 10.1103/physrevb.69.134401
|View full text |Cite
|
Sign up to set email alerts
|

Spin waves in an inhomogeneously magnetized stripe

Abstract: We have observed collective spin-wave modes in inhomogeneously magnetized Ni 0.81 Fe 0.19 thin-film stripes. The stripes, 18 nm thick and 2 m wide, are studied in an in-plane magnetic field oriented along their short axes. When the magnetic field is on the order of the shape anisotropy field, the equilibrium magnetization near the stripe edges rotates 90 deg over a length scale of order 100 nm-1 m. Time-resolved Kerr microscopy is used to detect a hierarchy of spin-wave modes in these edge regions. Using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 19 publications
3
89
0
Order By: Relevance
“…The self-focusing was attributed to the interference of the copropagating 1 st -and 3 rd -order modes and viewed as a potentially usable means for efficient transmission of microwave signals. 31,34 In addition, Bayer et al 37 and Topp et al 38 investigated spin-wave spectra of a magnetic waveguide inhomogeneously magnetized in the transverse direction. These studies indicated that the spin-wave spectra of a transversely-magnetized magnetic waveguide are largely dependent on the size, shape, and boundary circumstance and the equilibrium magnetization distribution of the waveguide, the geometry of the utilized antenna, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The self-focusing was attributed to the interference of the copropagating 1 st -and 3 rd -order modes and viewed as a potentially usable means for efficient transmission of microwave signals. 31,34 In addition, Bayer et al 37 and Topp et al 38 investigated spin-wave spectra of a magnetic waveguide inhomogeneously magnetized in the transverse direction. These studies indicated that the spin-wave spectra of a transversely-magnetized magnetic waveguide are largely dependent on the size, shape, and boundary circumstance and the equilibrium magnetization distribution of the waveguide, the geometry of the utilized antenna, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This creates a varying magnetization profile across the width of the stripe [34], which has been used to explain that the spin wave dispersion relation changes as a function of position [25,33,35]. Due to the varying demagnetizing field profile and stronger exchange interaction effects at the edges [32,34], a weaker effective field exists at the edges as compared to the center of the stripe and as a result, the frequencies of the edge mode are lower than that of the center mode.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…The aspect ratio (10:1) of the magnetic stripe is another factor that can affect the spin wave characteristics due to spatial confinement [14][15][16]32]. We study the effects of this parameter by carrying out measuring the spin wave characteristics at different distances from the left edge to the center of the stripe, as indicated by the red spot in the schematics of figures 3(a) and 3(b).…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Such studies are particularly important in view of the potential application of FM elements in magnetic data storage and microwave devices. [8][9][10][11] In many cases, however, magnetic elements do not stand alone, but are ͑par-tially͒ surrounded by metallic conductors.…”
Section: Introductionmentioning
confidence: 99%